The Mechanical Properties of Flax Fibre Reinforced Composites - YÜKSELOĞLU, SEVHAN MÜGE (SPRINGER, 2016)
Generally, glass and carbon fibres are most widely used materials in composites. In this study it has been aimed to use flax fibres in composite materials and to study the mechanical properties of the produced samples. The research was carried out with 100 % unbleached flax fibres at different reinforcement ratios to produce hand lay-up composite materials. The produced composite samples were then characterized using three point bending and Izod impact tests. The fracture surfaces of the reinforced composite samples were also inspected with the help of SEM. Both the mechanical tests results (impact and three point bending) and SEM micrographs indicated flax fibres as an alternative natural fibre source for developing reinforced composites for various industries. Good mechanical properties i.e. 109-165 MPa were obtained as compared to the pure resin (approximate to 40 MPa). The flax fibre reinforced composites offered an impact strength of about 21-38 kJ/m(2). Finally, fibre/matrix-interface bonding in the composites was improved by the de-waxing process of flax fibres prior to composite fabrication.
Keywords: Flax fibers; Composites; Mechanical properties; Fracture surface; TENSILE